ITR: análise da norma de incidência, de isenção e dos deveres instrumentais - Arantes, Fernanda Teodoro (2018)
The present work intends to investigate the standard of incidence of rural territorial tax, exemption and instrumental duties. To do so, we first draw the method used for the elaboration of the work, as that of semantic logical constructivism, we establish premises and clarify fundamental concepts defining them. We address the criteria of the tax incidence rule-array, delving deeper into its general theory to apply to the construction of the rule-array of tax incidence of the rural territorial tax. When constructing this norm of behavior, we have made a split between the fiscal and extra-fiscal rules, in order to analyze carefully all its structure. We find a very complex tax, in the construction of all its criteria from the antecedent of the norm, which are: material (concept of property and rural property), spatial (between destination and location) and temporal, as well as (passive and active) (quantitative or not) and quantitative (exemption, non-incidence, principle of contributory capacity, isonomy, non-confiscation). The division of the norm of behavior allowed us to verify the strict relation of the extrafiscal tax rate with the materiality that authorizes it, what is the exercise of the social function. The analysis of the exemption rules led us to also investigate the institute of non-incidence and its application in this tax, as well as to observe its structure as a standard of structure. The duties of presenting the ADA, CAR, and registering the legal reserve in enrollment, instigated us to classify them as instrumental duties of the exemption rules, which had repercussions in the analysis of the imposed sanction. We conclude with the analysis of some practical cases, such as the incidence of ITR in the areas of mineral exploration, landfill and embargoed for any activity by competent agent. To conclude we made our final considerations exploring the main constructions realized on the subject